Phenomenological considerations on empathy and emotions in psychotherapy - Irarrázaval, Leonor; Kalawski, Juan Pablo (Frontiers in Psychology, 2022)
In this article we will present a phenomenological approach to empathy and its relationship with emotions in the context of psychotherapy, highlighting the importance of empathy as a key element of the therapist-client relationship and therapeutic process, beyond a specific psychological theory or model. We will use a consensus definition of empathy taken from phenomenologically oriented philosophy to analyze therapist's empathy, as well as client's self-empathy and their empathic communication with others. We will discuss emotions as they usually manifest in the context of psychotherapy, specifically describing how certain emotions can disturb empathic communication in close personal relationships and how it is possible to reestablish empathic communication in psychotherapy. This article it is not only based on evidence from scientific literature but also incorporates the authors’ practical knowledge of psychotherapy.